Math CentralQuandaries & Queries


Question from Enid, a student:

Solve by substitution method
3x + 7y = 25
-7x + y = 63

Hi Enid,

This problem is especially nice for the substitution method. In the second equation the coefficient of y is 1 so it is straightforward to solve this equation for y.

-7x + y = 63 so y = 63 + 7x

Substitute y = 63 + 7x into the first equation. Thus

3x + 7y = 25

so after substitution

3x + 7(63 + 7x) = 25

Solve for x and then substitute the value you get into either of the original equations and solve for y.


About Math Central


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences.
Quandaries & Queries page Home page University of Regina PIMS